Independent elevation of peripheral oxytocin concentrations and reduction in cognitive empathy during 4‐fluoroamphetamine intoxication. (25th October 2018) - Dolder, Patrick C.; de Sousa Fernandes Perna, Elizabeth B.; Mason, Natasha L.; Hutten, Nadia R. P. W.; Toennes, Stefan W.; Theunissen, Eef L.; Ramaekers, Johannes G.; Kuypers, Kim P. C.
Abstract: Objectives: 4‐Fluoroamphetamine (4‐FA) is a novel psychoactive substance with a pharmacological profile and reported subjective effects (e.g., empathy) intermediate between 3, 4‐methylenedioxymethamphetamine (MDMA) and amphetamine. Studies have shown that MDMA and amphetamine increase emotional empathy without affecting cognitive empathy; MDMA simultaneously leads to elevated levels of oxytocin, unrelated to its behavioral effects. The aim of the present study was to assess the reported enhancement of empathy by 4‐FA, to assess its effects on oxytocin, and to test potential associations between both. Methods: Twelve healthy poly‐drug users were included in a double‐blind placebo‐controlled two‐way crossover study. Treatments were 4‐FA (100 mg) and placebo; empathy was assessed by means of the multifaceted empathy test, and blood samples were taken before and after treatment administration to determine oxytocin concentrations. Results: 4‐FA reduced cognitive empathy, whereas emotional empathy was left unaffected. One hour after treatment, plasma oxytocin levels were significantly increased compared with placebo. Behavioral and hormonal effects were unrelated. Conclusion: Although 4‐FA shares its pharmacological mechanism with MDMA and amphetamine, current findings seem to indicate that it affects empathy differently. The 4‐FA‐induced increase in oxytocin levels was independent of behavioral effects, which confirms previous findings that drug‐induced effects on peripheral oxytocin levels are not associated with empathy.